Sistema básico de automação de manutenção e monitoramento de aquários domésticos para peixes ornamentais Guppy - Nunes, Elen da Silva (2020)
This paper demonstrates the development of a basic automation system for the maintenance and monitoring of domestic aquariums for ornamental fish Guppy. The purpose of this paper is to demonstrate the possibility of developing a system using a Raspberry Pi computer to program the automation of tasks related to the maintenance of a domestic aquarium, such as fish feeding, aquarium illumination, heating and water oxygenation. The present paper is divided into four primary sections: theoretical framework, methodology, project realization and tests and results obtained. The first section presents a review of the subjects of interest for the development of this paper, which are: the Guppy fish, to delimit the system's operating parameters; the most important devices for the maintenance of an aquarium such as air pump, illuminator, feeder, heater; the Raspberry Pi, the relay and the Phyton programming language. The second section is the methodology in which are the steps and materials necessary for the creation of the aquarium and the algorithm. The third section is the realization of the project that performs the steps proposed in the methodology. The fourth section is the tests and results obtained, which describes the behaviors observed during the testing of the program and its implementation. And finally, in the conclusion it is found that it is possible to create a basic system for the maintenance of home aquariums for ornamental fish Guppy.